A study of the impact of building geometry on the thermal performance of road pavement solar collectors - Nasir, Diana S.N.M.; Hughes, Ben Richard; Calautit, John Kaiser (Elsevier, 2015)
Studies on RPSC (road pavement solar collectors) have shown the potential of reducing the UHI (urban heat island) effects by dissipating the heat from the pavement for energy harness. Several works have shown that the generated heat could be utilised for sustainable urban energy system. However, none of the previous literatures have assessed the effect of building geometry on the performance of the RPSC. This study investigates the thermal performance of an urban-integrated RPSC system by using CFD (computational fluid dynamic) simulation of integrated RPSC system with a standard urban canyon domain and an empty domain. Based on 21st June at 13:00, it was found that the RPSC system in urban canyon domain was on average 36.08% more effective in thermal collection and provided on average 27.11% more surface temperature reduction as compared to the RSPC application in rural/flat domain. The RPSC performance based on the effect from daily solar intensity was initiated with results demonstrated the efficiency of the RPSC in an urban setting was 7.14%–63.26% more than the rural/flat setting. Simulations of various wind speeds in summer day(s) and the impact of seasonal changes to the RPSC system were also conducted to investigate the deficiency factors to the system.